La destinazione dei beni confiscati alle mafie nell'Unione Europea Normative e prassi applicative a confronto - Costantino, Salvatore (Communicazioni, Istituzioni, Mutamento Social - Open Access, 2018)
The volume compares the legislation and the application practice regarding administration and destination in the EU. Then the main experiences of social reuse and reuse regimes are presented, with a focus on the Italian (direct social reuse) and French (indirect social reuse) cases.